Editors’ Foreword - Elmaz, Orhan (Proceedings of the Seminar for Arabian Studies, 2015)
The Seminar for Arabian Studies is the only international academic forum which meets annually for the presentation of research in the humanities on the Arabian Peninsula. It focuses on the fields of archaeology, architecture, art, epigraphy, ethnography, history, language, linguistics, literature, and numismatics from the earliest times to the present day.